2015
DOI: 10.1111/jre.12317
|View full text |Cite
|
Sign up to set email alerts
|

A novel large deletion combined with a nonsense mutation in a Chinese child with Papillon–Lefèvre syndrome

Abstract: Our study reveals a compound mutation consisting of a large deletion and a nonsense mutation, which provides a new insight in the mutation type of CTSC gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Among the Chinese patients with CTSC gene variants, one patient showed physical retardation (Wu et al, 2019 ). It was worth noting that one patient manifested skin abnormalities at 1 week after she was born, and this finding was earlier than most previous reports (Wu et al, 2016 ). In addition, Wang et al first reported that serum levels of IgE were significantly increased in a PLS patient and the serum IgE subsequently decreased in tune with the recovery of periodontitis (Wang et al, 2015 ; Wen et al, 2012 ).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Among the Chinese patients with CTSC gene variants, one patient showed physical retardation (Wu et al, 2019 ). It was worth noting that one patient manifested skin abnormalities at 1 week after she was born, and this finding was earlier than most previous reports (Wu et al, 2016 ). In addition, Wang et al first reported that serum levels of IgE were significantly increased in a PLS patient and the serum IgE subsequently decreased in tune with the recovery of periodontitis (Wang et al, 2015 ; Wen et al, 2012 ).…”
Section: Discussionsupporting
confidence: 46%
“…In addition to these basic features, patients with PLS also can present with mild mental retardation, intracranial calcifications, nail dystrophy, etc. About 20%–25% of PLS patients increased susceptibility to microbial infections, such as skin abscess, kidney abscess, or liver abscess (Wu et al, 2016 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cathepsin C activity is proposed to play a key role in the epithelial differentiation and desquamation, while the inappropriate genetic alterations may result in nearly complete loss of cathepsin C enzymatic activity in homozygous individuals with the disease, or correspondently reduced activity of the enzyme in the family members who are heterozygous carriers [36,37]. The present research group reported a PLS patient with a 110 kb deletion (Chr11: 88032292:88142997 [NC_000011]) and a nonsense mutation exists (Gln182Ter, CAG > TAG) in the fourth exon of the CTSC gene [38].…”
Section: Etiology and Pathogenesismentioning
confidence: 87%
“…Patients with PLS present first clinical signs in the oral cavity as soon as the deciduous teeth erupt [34,36]. Oral manifestations become apparent by the age of 2 to 3 years with rapid periodontal destruction: plaque accumulation, obvious gingival inflammation and bleeding, periodontal abscess, deep periodontal pocket formation, alveolar bone resorption, loose teeth, halitosis, following by premature exfoliation of all deciduous teeth by the age of 4 to 5 years (Figure 7) [38]. Radiographic investigations show generalized alveolar bone loss and migration of teeth whit no evidence of root resorption (Figure 8).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Other symptoms of PLS are hyperhidrosis, intracranial calcification, arachnodactyly, increased susceptibility to infections, hearing loss, mental retardation, oculocutaneous albinism, bent nail syndrome, corneal cell hyperkeratosis, acanthosis nigricans, thicker cutaneous granular layer, etc (Almuneef, Al Khenaizan, Al Ajaji, & Al-Anazi, 2003;Borroni et al, 1985;Farkas et al, 2013;Haneke, 1979;Khandpur & Reddy, 2001;Oguzkurt, Tanyel, Büyükpamukçu, & Hiçsönmez, 1996;Basapogu Sreeramulu et al, 2015;Tosti, Manuzzi, Bardazzi, & Costa, 1988;Wani, Devkar, Patole, & Shouche, 2006;Wu et al, 2016). Furthermore, this disorder may also be accompanied with other symptoms such as the skin, liver, kidneys and brain abscesses(R J Gorlin et al, 1964;Kanthimathinathan et al, 2013;Mercy, Singh, Ghorpade, Das, & Upadhyay, 2013;Morgan, Hannon, & Lakhoo, 2011).…”
Section: Introductionmentioning
confidence: 99%